2015
DOI: 10.1038/ncomms9090
|View full text |Cite
|
Sign up to set email alerts
|

The precision of value-based choices depends causally on fronto-parietal phase coupling

Abstract: Which meal would you like today, chicken or pasta? For such value-based choices, organisms must flexibly integrate various types of sensory information about internal states and the environment to transform them into actions. Recent accounts suggest that these choice-relevant processes are mediated by information transfer between functionally specialized but spatially distributed brain regions in parietal and prefrontal cortex; however, it remains unclear whether such fronto-parietal communication is causally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
135
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 53 publications
17
135
1
2
Order By: Relevance
“…The role of leptin in feeding is known to be complex. One recent study has shown that communication between frontal and parietal regions plays a role in value-based choices [58]. The relationship of leptin with pre-SMA, motor cortex, parietal cortex, and precuneus that we observed in this study could suggest a potential role for leptin in those complex neuronal circuits which evaluate food choices.…”
Section: Discussionsupporting
confidence: 60%
“…The role of leptin in feeding is known to be complex. One recent study has shown that communication between frontal and parietal regions plays a role in value-based choices [58]. The relationship of leptin with pre-SMA, motor cortex, parietal cortex, and precuneus that we observed in this study could suggest a potential role for leptin in those complex neuronal circuits which evaluate food choices.…”
Section: Discussionsupporting
confidence: 60%
“…Many studies have established relationships between diffusion models and neurophysiological measures such as single cell recordings in rodents and monkeys [52,88,105,145-150], electroencephalography (EEG) [42-43,151,153], functional magnetic resonance imaging (fMRI) [42-43,141,152,154-157], transcranial magnetic stimulation (TMS) [158], transcranial alternating current stimulation (tACS) [159]. Diffusion model analyses have also been applied to bees and animal swarms [160-161] and even to slime moulds [162].…”
Section: Figurementioning
confidence: 99%
“…This and other diffusion models have been used to account for, among other things, value-based decision, social choice, and purchasing decisions [153-155,159,208-211]…”
Section: Figurementioning
confidence: 99%
“…This parallel may be somewhat exaggerated, however, as emotion and reward are sometimes experimentally operationalized similarly, and thus would produce similar effects in behavior. Specifically, both emotion and reward are often studied using shocks (Bauch et al, 2014;Bisby & Burgess, 2014;Dunsmoor et al, 2015;Jensen et al, 2007;Murty et al, 2012Murty et al, , 2011Pessoa, 2009;Phelps & LeDoux, 2005;Redondo et al, 2014;Schmidt et al, 2015;Wang et al, 2013;Weiner & Walker, 1966), food (Beaver et al, 2006;de Water et al, 2017;Isen & Geva, 1987;LaBar et al, 2001;Polanía et al, 2015;Talmi et al, 2013;Wadlinger & Isaacowitz, 2006), emotional face pictures (Bradley et al, 1997;Lin et al, 2012;Tsukiura & Cabeza, 2008;Vrijsen et al, 2013;Vuilleumier & Schwartz, 2001;Woud et al, 2013), or erotic/sexual pictures (Attard-Johnson & Bindemann, 2017;Bradley et al, 2001;Ferrey et al, 2012;Hamann et al, 2004;Iigaya et al, 2016;Most et al, 2007;Sescousse et al, 2013aSescousse et al, , 2010. As such, it would be expected that both emotion and reward demonstrate similar effects on cognition, as they can be studied using nearly identical experimental designs.…”
mentioning
confidence: 99%